Highly catalytic nanoenzyme of covalent organic framework loaded starch- surface-enhanced Raman scattering/absorption bi-mode peptide as biosensor for ultratrace determination of cadmium - Li, Jingjing; Shu, Yiyi; Li, Chongning; Jiang, Zhiliang (Frontiers in Nutrition, 2023)
High affinity peptides (PTs) have been used in nanoanalysis, but there are no reports which combine PTs with a liquid crystal (LC) covalent organic framework (COF) supported soluble starch (SS) catalytic amplification system as a biosensor recognition element. In this study, a new, highly sensitive and selective bi-mode molecular biosensor has been developed for the determination of cadmium ion (Cd2+). Specifically, a highly catalytic and stable COF supported SS nanosol catalyst was fabricated such that a nanocatalytic indicator reaction system for HAuCl4-sodium formate was established based on surface-enhanced Raman scattering (SERS). The Au nanoparticles produced exhibited a surface plasmon resonance (SPR) absorption peak at 535 nm and a SERS peak at 1,615 cm–1. Combining the nanocatalytic amplification indicator system with the specific PTs reaction permitted a sensitive and selective SERS/absorption bi-mode platform to be developed for the determination of cadmium in rice. The linear range for SERS determination was 0.025–0.95 nmol/L and the detection limit (DL) was 0.012 nmol/L.